ETHNOMATHEMATICAL ASPECTS OF LEARNING GEOMETRY AND VALUES RELATED TO THE MOTIFS USED BY THE DAYAK NGAJU TRIBE IN CENTRAL KALIMANTAN (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Ethnomathematics are used in motifs by the Dayak Ngaju Tribe in Central Kalimantan. The motifs contain someEthnomathematical objects and concepts for Geometry and values. Therefore, this study aimed to describe the motifs based onmathematical objects and concepts of Geometry and value viewed from ethnomathematics aspects.Methodology – This study used a qualitative approach with an ethnography method. The researchers collected information fromdocuments and books. They conducted in-depth observations and interviews with the subjects regarding the culture of the Dayak Ngaju people who reside downstream of the Kahayan River in Central Kalimantan. The subjects were a Dayak Ngaju craftsman and a priest of the Hindu Kaharingan community. The motifs consist of tingang, dandang tingang, jata, batang garing, tanduk muang, buntut kakupu gajah, taya tree and rambunan tambun.Findings – The motifs contain some mathematical objects and concepts. Mathematical objects are created as circles, batang garingand jata motifs, and a six-sided shape in the tanduk muang motif. The concept is the geometric transformations, namely in the mdandang tingang and tanduk muang motifs the reflection in the motifs of tingang, batang garing, tanduk muang and taya tree. The on point (0,0) in the motifs of buntut kakupu gajah and taya tree, and the translation in the motif of jata.Significance – The study provides some mathematical objects and concepts in the motifs of the Dayak Ngaju tribe in Central Kalimantan. Students learning those objects and concepts should be related to their culture, namely the motifs, and they should acquire the values in such learning. Ethnomathematics plays an important role among Dayak Ngaju people in understanding mathematics concepts such as Geometry and values.